The Disentanglement of Populations
XXVIII, 351 p.
Keywords: An examination of population movements, both forced and voluntary, within the broader context of Europe in the aftermath of the Second World War, in both Western and Eastern Europe. The authors bring to life problems of war and post-war chaos, and assess lasting social, political and demographic consequences.